Penerapan model pembelajaran discovery learning dengan metode outdoor dalam meningkatkan aktivitas dan hasil belajar - Ni Luh Putu Evayani (Indonesian Journal of Educational Development, 2020)
Research on classroom actions is motivated by: (1) student learning outcomes are still relatively low ; (2) the learning activities of students are less active, (3) the method of learning to descend is still conventional; and (4) students do not yet have good motivation to learn. This condition wants to be changed through the application of discovery learning learning models with outdoor methods. The purpose of this study was to determine the effectiveness of the application of the discovery learning model of learning with the oudoor method in an effort to increase the activities and learning outcomes in the subject of Chemistry. Classroom Action Research was carried out in 2 cycles of each cycle with the main steps: planning, acting, observing, raftakting with always revise actions to find better results or skunt. Data processing using descriptive analytical techniques. With the action research procedure carried out, it is found that the results are as follows: (1) the application of discovery learning learning models with outdoor methods can be said to be effectively applied to increase activity and learning outcomes in lessons are proven from the results of research in cycles 1, and 11 with the average value of student learning outcomes increased from 6945 to 77.17 and classical learning excellence also increased from 58%, to 94%. Penelitian tindakan kelas ini dilatarbelakangi oleh: (1) hasil belajar siswa masih tergolong rendah; (2) aktivitas belajar siswa kurang aktif; (3) metode pembelajaran guru cenderung masih konvensional; dan (4) siswa belum memiliki motivasi belajar yang baik. Kondisi ini ingin diubah melalui penerapan model pembelajaran discovery learning dengan metode outdoor. Tujuan penelitian adalah untuk mengetahui tingkat efektivitas penerapan model pembelajaran discovery learning dengan metode outdoor dalam upaya meningkatkan aktivitas dan hasil belajar. Penelitian tindakan kelas ini dilaksanakan dalam 2 siklus. Setiap siklus dengan langkah-langkah pokok: planning, acting, observing, reflekting dengan selalu melakukan revisi tindakan untuk menemukan hasil yang lebih baik atau akurat. Pengolahan datanya menggunakan teknik deskriptif analitis. Dengan prosedur penelitian tindakan yang dilakukan, ditemukan hasil sebagai berikut: (1) penerapan model pembelajaran discovery learning dengan metode outdoor dapat dikatakan efektif diterapkan untuk meningkatkan aktivitas dan hasil belajar yang dibuktikan dari hasil penelitian pada siklus I, dan II dengan nilai rata-rata hasil belajar peserta didik kelas meningkat dari 65,45 menjadi 77,17 serta ketuntasan belajar klasikal juga meningkat dari 58%, menjadi 94%.